A identidade de gênero no espaço escolar: aportes psicanalíticos à prática pedagógica - Kurpel, Denise de Fatima. (2019)
The present research aims at the gender identity in the school space, in which psychoanalytic contributions were emphasized to the pedagogical practices. We carried out a bibliographical research in the public universities of the state of Paraná, to identify how many and which are the researches developed that include the construction of gender identity, school sex education and psychoanalysis. We seek to discuss gender identity in school spaces through the history of how the gender was constituted in Western society, presenting elements that help in the economic, social and cultural construction of this. The databases we selected for the development of the research and later the theoretical-bibliographic review were: Digital Library of Theses and Dissertations (BDTD), Public Domain, Coordination of Improvement of Higher Level Personnel (CAPES) and Digital Libraries of public universities in the state of Paraná. Among the scientific productions stricto senso found and selected through the predefined inclusion and exclusion criteria, we selected twenty-seven (27) master's dissertations from the pre-category "gender and personal identity"; four (04) dissertations from the pre-category "gender identity and biology"; one (01) dissertation from the pre-category "gender identity and psychoanalysis" and eleven (11) dissertations from the pre-category "gender identity and school sex education". Our research is justified by the absence of productions that approach psychoanalytic science in school spaces, regarding the identity of cis and trans gender. We have developed a brief historical background on gender and identity, as well as the definitions that have been constructed throughout history by the first and second wave feminist movements. From the perspective of historical and dialectical materialism, we present the political debates in Brazil about the gender identity in the school space and its direct relation with the project "School Without Party". We demonstrate, in the course of our research, the influence of biological sciences on sexuality discourses and gender identity of trans people, and we approach psychoanalytic science, critiques, limits and possibilities for its use as a pedagogical support that can aid in understanding of our research object. Finally, we highlight the resolutions that are used by psychologists to assist in the depatologization of gender identity and the applicability of psychoanalytic concepts in school spaces, together with sexual education